Can sleep disturbance be a cue of mood spectrum comorbidity? A preliminary study in panic disorder. (February 2020) - Miniati, Mario; Palagini, Laura; Maglio, Alessandra; Marazziti, Donatella; Dell'Osso, Liliana
Abstract : Objective: To investigate if sleep disturbances may affect treatment outcomes of patients with panic disorder (PD). Methods: Eighty-five PD outpatients with no Axis I comorbidity for mood disorders completed a baseline assessment (T1) and were evaluated after 3 (T2), 6 (T3) and 12 months (T4), with the Panic Disorder Severity Scale (PDSS) total score as outcome measure during a 12-month naturalistic follow-up. Patients were assessed with the Mood Spectrum Self-Report (MOODS-SR, Lifetime Version), and the PDSS. Results: Forty-three patients (50.5%) met criteria for remission (PDSS<5) and 42 (49.5%) for no remission. In a logistic regression model with remission as the dependent variable, MOODS-SR sleep disturbances was the only determinant for a lower likelihood of PD remission. The items accounting for this result were the following: Repeated difficulty falling asleep (chi-square = 4.4; df = 1; p = 0.036), and Repeatedly waking up in the middle of the night (chi-square = 5.2; df = 1; p = 0.022). Conclusion: Lifetime sleep disturbances would represent a cue of mood spectrum (in absence of overt affective comorbidity) that may impair remission in PD.